PENANGANAN PERMUKIMAN KUMUH MELALUI PEMBANGUNAN RUSUNAWA: STUDI KASUS RUSUNAWA KALIGAWE, KOTA SEMARANG - Alva Ayu Octavionesti; Fadjar Hari Mardiansjah (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
Shelter is one of the most basic human needs. The high valuable asset of shelter makes it difficult to be reached by the people. In the urban areas, the limited supply and low affordability of the people tend to create slum and squatter settlements. In dealing with the slum and squatter settlements, the government provides decent housing for the low income people by using low cost rental apartment as one of the approachs. The purpose of this research is to evaluate the otential of Rusunawa (low cost rental appartment) program as one form of urban housing policy in providing low income housing for those who previously live in slum and suatter settlements.The research used descriptive quantitative method by collecting primary data from the residents of Rusunawa Kaligawe by using questionnaire. The study also conducted field observations, interviews, and secondary data collection that were obtained to strengthen the study. The results of this study show that most residents Rusunawa feel that rusunawa have better conditions compared with previous residence, supported by the availability of better infrastructure and facilities. However, one of the weaknesses is that there are no educational facilities, especially junior and senior high schools, provided around the Rusunawa. The Rusunawa Program is an effective program dealing with the urban slums and squattera problems. Rusunawa development can have more potential since it can also be expected to improve the quality of the neighborhoods through the township development approach. Rusunawa development can also be directed to a more human urban development, in addition to be the solution to improve the quality of settlements due to the availability of better and adequate facilities and infrastructure. Therefore, the development of rusunawa should be integrated into the development of residential development so as to be capable in providing the supporting facilities needed in the neighborhood